Role of the Extracellular and Intracellular Loops of Follicle-Stimulating Hormone Receptor in Its Function - Banerjee, Antara A.; Mahale, Smita D. (Frontiers in Endocrinology, 2015)
Follicle stimulating hormone receptor (FSHR) is a leucine rich repeat containing class A G-protein coupled receptor belonging to the subfamily of glycoprotein hormone receptors, which includes luteinizing hormone/choriogonadotropin receptor (LH/CGR) and thyroid stimulating hormone receptor (TSHR). Its cognate ligand, follicle stimulating hormone (FSH) binds to and activates FSHR expressed on the surface of granulosa cells of the ovary, in females, and Sertoli cells of the testis, in males, to bring about folliculogenesis and spermatogenesis, respectively. FSHR contains a large extracellular domain (ECD) consisting of leucine rich repeats at the N-terminal end and a hinge region at the C-terminus that connects the ECD to the membrane spanning transmembrane domain (TMD). The TMD consists of seven α-helices that are connected to each other by means of three extracellular loops (ELs) and three intracellular loops (ILs) and ends in a short cytoplasmic tail. It is well established that the extracellular domain (ECD) is the primary hormone binding domain, whereas the TMD is the signal transducing domain. However, several studies on the ELs and ILs employing site directed mutagenesis, generation of chimeric receptors and in vitro characterization of naturally occurring mutations have proven their indispensable role in FSHR function. Their role in every phase of the life cycle of the receptor like post translational modifications, cell surface trafficking, hormone binding, activation of downstream signaling, receptor phosphorylation, hormone-receptor internalization, recycling of hormone receptor complex have been documented. Mutations in the loops causing dysregulation of these processes lead to pathophysiological conditions. In other GPHRs as well, the loops have been convincingly shown to contribute to various aspects of receptor function. This review article attempts to summarize the extensive contributions of FSHR loops and C-terminal tail to its function.